2018
DOI: 10.1007/s12020-018-1671-8
|View full text |Cite
|
Sign up to set email alerts
|

Low trabecular bone score in postmenopausal women with differentiated thyroid carcinoma after long-term TSH suppressive therapy

Abstract: Longer-term suppression therapy in female patients with DTC did not increase significantly the risk of bone loss, although we found in postmenopausal patients deterioration of bone microarchitecture. TBS study should be considered in the evaluation of postmenopausal DTC patients on long-term DTC for the evaluation of the risk of fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
6
20
1
Order By: Relevance
“…The comparative study concerning pre-and postmenopausal patients with differentiated thyroid carcinoma (DTC) receiving long-term TSH suppressive therapy (TST) revealed that postmenopausal women with DTC receiving TST had lover TBS, compared to premenopausal patients. These TBS changes did not co-occur with BMD loss [53]. Similar results concerning TST in group of postmenopausal DTC patients were confirmed by other authors, also indicating that more than five years of TST resulted in lower lumbar spine TBS values compared to patients with therapy of less than three years (1.335 ± 0.092 vs. 1.296 ± 0.078, p = 0.015) [54].…”
Section: Thyroid Diseasessupporting
confidence: 84%
See 1 more Smart Citation
“…The comparative study concerning pre-and postmenopausal patients with differentiated thyroid carcinoma (DTC) receiving long-term TSH suppressive therapy (TST) revealed that postmenopausal women with DTC receiving TST had lover TBS, compared to premenopausal patients. These TBS changes did not co-occur with BMD loss [53]. Similar results concerning TST in group of postmenopausal DTC patients were confirmed by other authors, also indicating that more than five years of TST resulted in lower lumbar spine TBS values compared to patients with therapy of less than three years (1.335 ± 0.092 vs. 1.296 ± 0.078, p = 0.015) [54].…”
Section: Thyroid Diseasessupporting
confidence: 84%
“…Trabecular bone score cut-off points classifying normal and abnormal TBS values have not yet been defined. The only available TBS range is one that has been proposed for postmenopausal women [21][22][23].…”
Section: Tbs Evaluation Resultsmentioning
confidence: 99%
“…De Mingo Dominguez et al analyzed BMD, TBS, and bone turnover markers in 61 premenopausal and 84 postmenopausal Caucasian women at baseline (within 3 months after total thyroidectomy) and after 10 years of TSH suppressive therapy. Postmenopausal women showed a lower TBS compared to premenopausal women and there was no correlation between changes in TBS and BMD (46). In another retrospective cohort study involving 273 postmenopausal women with DTC treated with TSH suppressive therapy, Moon et al showed that TSH suppressive therapy was associated with lower TBS and this association was independent of age, BMI, and BMD (47).…”
Section: Trabecular Bone Score (Tbs) and Quantitative Computed Tomogrmentioning
confidence: 99%
“…Only three studies analyzed the effect of thyroid function on TBS. In two prospective cohorts of participants with thyroid cancer undergoing TSH suppressive therapy for 5 to 10 years [26,27], excess LT4 treatment had a deleterious effect on TBS only in women transitioning from pre-to post-menopause [26], and no effect in post-menopausal women at treatment initiation [26,27]. But in a euthyroid cohort [28] high-normal free T4 levels, but not TSH values, were associated with low TBS only in post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%